Implementasi Peraturan Bupati No 58 Tahun 2014 terhadap Pengelolaan Arsip di Dinas Kearsipan Kabupaten Badung - Anak Agung Dinda Trisna Kesumadewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
Archiving has an important role for running of an administration process of an organization. Archiving serves as a source of information and monitoring tools which are needed by every organization in making reports, accountability, assessment and control as precisely as possible. The problems in this study are: 1) How does the process of arrangement active and inactive dynamic archive in the Archive Management Unit in Archives and Library Service Badung Regency in accordance with Badung Regent Regulation Number 58 of 2014? 2) What efforts are made by the Archives and Library Service Badung Regency so that every government agency in the Badung Regency Government implements the Badung Regent Regulation No. 58 of 2014 in the management of archive?. The technique of collecting the data was done by using the method of recording. Data is then analyzed using systematic legal interpretation and legal arguments based on deductive logic. The conclusions of this study are: 1) the process of active and inactive dynamic archive arrangement in the Badung Regency Archives and Library Management Unit is to use classification codes and indexes. 2) Obstacles and Library Constraints in implementing Regent Regulation No. 58 of 2014 is that people's thoughts on filing are not well understood, facilities and infrastructure are still lacking, management staff at each SKPD do not understand about archival management, and Head of Service at each SKPD is less concerned with archive management personnel. The efforts of the Department of Archives in implementing Regent Regulation No. 58 of 2014 are by developing archival human resources, archiving socialization, archiving guidance, and community participation.